Computer Assisted Turkish Based Media Content Analysis System - Project 107K209: A Case Study - Arıkan, Aykut (Information World, 2009)
Content analysis is a well-described systematic strategy of inquiry to the analyzed media content object, or in other words, to a communication text. From the very beginning of the research it must be described what is looked after. Theoretic explanations of content analyses sometimes differ from practical usage. Research based on content analysis, requires steps, techniques and processes to fix the research on an adequate foundation and to save time and work. A group of researches at Yeditepe University decided to develop a computer assisted content analysis system for Turkish media content. The project was proposed to TUBITAK (The Scientific and Technological Research Council of Turkey) in form of a scientific research project under the project number 107K209. The project makes use of two scientific methods: Content analysis and information retrieval. In addition to these, quality management is adopted, to reach effective results. All these methodological approaches are driven together as a system design within the systems approach. The purpose of this report is to deliver primary information on the project and to discus methodological, scientific and applied problems and issues related to the project. The nature of the report is descriptive by making use of scientific methods and techniques such as historical description, systems modeling, and the like. The application of content analysis, linguistic, and information retrieval methodologies will be the focal point of the discussion.